The Role of Social Media Marketing in Building Customer Loyalty among Millennials - Frans Sudirjo; Dasa Rahardjo Soesanto (Westscience Press, 2025)
This study investigates the role of social media marketing in building customer loyalty among Indonesian millennials. A quantitative research approach was employed to examine the relationship between social media marketing activities and customer loyalty. Data were collected from 150 Indonesian millennial respondents who actively use social media and engage with brand-related content. The measurement instrument used a five-point Likert scale, and the collected data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 25. The results of simple linear regression analysis indicate that social media marketing has a positive and significant effect on customer loyalty, with a regression coefficient of 0.693 and a significance value below 0.05. The coefficient of determination (R²) of 0.445 suggests that social media marketing explains 44.5% of the variance in customer loyalty. These findings highlight the importance of content quality, interaction, information sharing, and trust in strengthening long-term relationships with millennial consumers. The study provides practical implications for businesses in Indonesia to optimize social media marketing strategies in order to enhance customer loyalty and sustain competitive advantage in the digital marketplace.